2012
DOI: 10.1371/journal.pone.0035515
|View full text |Cite
|
Sign up to set email alerts
|

Self Care Behavior among Patients with Diabetes in Harari, Eastern Ethiopia: The Health Belief Model Perspective

Abstract: BackgroundDiabetes mellitus is a chronic disease that requires lifelong medical treatments and a life style adjustment. To prevent serious morbidity and mortality, it requires dedication to demanding self-care behaviors in multiple domains. The objective of this study was to identify predictors of self care behaviors among patients with diabetes.MethodsFrom a total of 425 follow up diabetic patients, a quantitative cross sectional study was conducted among 222 of them from three different hospitals in Harar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
153
16
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(227 citation statements)
references
References 16 publications
(22 reference statements)
45
153
16
6
Order By: Relevance
“…This finding was in line with the research result conducted of [7]) at the Endocrine Clinic DR Hasan Sadikin that the majority of patients (55.91%) belong to low level self care. Meanwhile Reference [12] conducted a research to assess diabetic patients' understanding about selfcare knowledge, concluded that in general the level of self-care behavior of diabetic patients is poor (unsatisfactory). Although the significance varies among countries, less optimum self-care behaviors among DM patients nearly exist in all countries.…”
Section: Self Care Behavior Of the Patients With Type 2 Diabetementioning
confidence: 99%
“…This finding was in line with the research result conducted of [7]) at the Endocrine Clinic DR Hasan Sadikin that the majority of patients (55.91%) belong to low level self care. Meanwhile Reference [12] conducted a research to assess diabetic patients' understanding about selfcare knowledge, concluded that in general the level of self-care behavior of diabetic patients is poor (unsatisfactory). Although the significance varies among countries, less optimum self-care behaviors among DM patients nearly exist in all countries.…”
Section: Self Care Behavior Of the Patients With Type 2 Diabetementioning
confidence: 99%
“…According to the WHO, insufficient physical activity, defined as less than 150 minutes of moderate physical activity per week [or equivalent], was present in about a quarter of men and a third of women in African region [46,47]. A similar study done in Harari, Ethiopia, showed that only 31.1% had exercise for thirty minutes per day [48].…”
Section: Idf Atlasmentioning
confidence: 99%
“…(2) Non-adherence to the treatment of diabetes mellitus is a problem whose dimensions are renowned in the international and Brazilian contexts, contributes to the low efficiency level of the treatment with complications in the medium and long-term and, consequently, increases the demand for high-complexity health services. (2)(3)(4)(5) The prevalence of non-adherence shows great variation depending on the study design, research population and measuring method. In the literature, the rates vary between 17% and 86% for medication treatment, 62% to 71% for the diet and 47% to 80% for physical exercise.…”
Section: Introductionmentioning
confidence: 99%